PERAN SHALAT DHUHA DAN MUSAFAHAH DALAM MEMBENTUK AKHLAKUL KARIMAH - Saniyah, Minhatus (FORPIM PTKIS ZONA TAPAL KUDA, 2025)
This study aims to examine the role of habitual dhuha prayer and musafahah (handshaking) in shaping students’ moral character (akhlakul karimah) at MI An-Nidhom Kebunrejo Genteng. The research focuses on integrating spiritual and social dimensions in developing students’ religious character. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation involving the principal, Islamic education teachers, and fourth to sixth-grade students. The findings reveal that dhuha prayer fosters students’ discipline, sincerity, and spiritual responsibility, while musafahah cultivates respect, empathy, and affection within the school community. The synergy of both activities creates a balance between hablun minallah (relationship with God) and hablun minannas (relationship with others), resulting in a harmonious and civilized religious character. This study reinforces the view that character formation in Islamic education is most effective through consistent religious practices and moral habituation rather than mere theoretical instruction.